Sex ratio rather than population size affects genetic diversity in Antennaria dioica. (30th March 2018) - Rosche, C.; Schrieber, K.; Lachmuth, S.; Durka, W.; Hirsch, H.; Wagner, V.; Schleuning, M.; Hensen, I.
Abstract: Habitat fragmentation and small population size can lead to genetic erosion in threatened plant populations. Classical theory implies that dioecy can counteract genetic erosion as it decreases the magnitude of inbreeding and genetic drift due to obligate outcrossing. However, in small populations, sex ratios may be strongly male‐ or female‐biased, leading to substantial reductions in effective population size. This may theoretically result in a unimodal relationship between sex ratios and genetic diversity; yet, empirical studies on this relationship are scarce. Using AFLP markers, we studied genetic diversity, structure and differentiation in 14 highly fragmented Antennaria dioica populations from the Central European lowlands. Our analyses focused on the relationship between sex ratio, population size and genetic diversity. Although most populations were small (mean: 35.5 patches), genetic diversity was moderately high. We found evidence for isolation‐by‐distance, but overall differentiation of the populations was rather weak. Females dominated 11 populations, which overall resulted in a slightly female‐biased sex ratio (61.5%). There was no significant relationship between population size and genetic diversity. The proportion of females was not unimodally but positively linearly related to genetic diversity. The high genetic diversity and low genetic differentiation suggest that A. dioica has been widely distributed in the Central European lowlands in the past, while fragmentation occurred only in the last decades. Sex ratio has more immediate consequences on genetic diversity than population size. An increasing proportion of females can increase genetic diversity in dioecious plants, probably due to a higher amount of sexual reproduction.